Pelatihan Aplikasi Data Kependudukan dan Surat Menyurat di Desa Jada Bahrin - Boy Dian Anugra Sandy; Endang Setyawati Hisyam; Yayuk Apriyanti; Indra Gunawan; M. Fikri Radiyan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Jada Bahrin is a village that is very different from other villages in Bangka Island which is famous for its tin mines. This village is famous for its plantations and agriculture. Because the location of the village is in the area of ​​plantations and agriculture, so many village officials or school administrators do not know or are unable to enter data into computers, both population data and write letters. Based on the situation analysis that has been explained, a problem that can be formulated in Jada Bahrin Village is the absence of training for the community to be able to use population applications and correspondence. With this training it is hoped that the village administration and the school can be better and easier to do archiving and data searching.